(70-5x)=(160-125x)

Simple and best practice solution for (70-5x)=(160-125x) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (70-5x)=(160-125x) equation:



(70-5x)=(160-125x)
We move all terms to the left:
(70-5x)-((160-125x))=0
We add all the numbers together, and all the variables
(-5x+70)-((-125x+160))=0
We get rid of parentheses
-5x-((-125x+160))+70=0
We calculate terms in parentheses: -((-125x+160)), so:
(-125x+160)
We get rid of parentheses
-125x+160
Back to the equation:
-(-125x+160)
We get rid of parentheses
-5x+125x-160+70=0
We add all the numbers together, and all the variables
120x-90=0
We move all terms containing x to the left, all other terms to the right
120x=90
x=90/120
x=3/4

See similar equations:

| 5t+15=-3.5 | | a/6=9/3 | | 14,00p+160p=24,000-200p | | 6=f+5 | | -4j+5-8+2j=21 | | 2(y-4)=4y-2 | | 3x-1=2x+5+10 | | 3.5x+8=12.5 | | 4/2=6/k | | 9x+4=10x-18 | | -4(4k-8)=80 | | 9/3=6/b | | f(1)=3(1)^2-6(1) | | 2r-6-32=50 | | 12.30=2g+3.54 | | 6x+59=38 | | 5(1+6n)=245 | | 2.4z+1.2z-6.5=0. | | (3x+31)=(2x-6 | | -29+z=38 | | 4u+3+2u+8=-25 | | 3n–9=2n+12 | | 60m+0.35=80m+0.25 | | 13+m=5 | | p=6,7p= | | 4(2)^x=0.5(4)^x | | 60m+0.35=80+0.25m | | 3(w-2)=3w+6 | | 9(2f-8)=-36 | | -4(1-6k)+8=-116 | | X-2(+13)=12x | | -4+7r-5=-44 |

Equations solver categories